Faktor-Faktor yang Mempengaruhi Kinerja Pegawai pada Kantor Dinas Kelautan dan Perikanan Kabupaten Takalar - Sirnan Sirnan; Sri Indira Hartawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of compensation and competence on employee performance at the office of marine and fisheries of Takalar Regency. The types of data used are qualitative data and quantitative data, then the data sources used are primary data and secondary data. The data analysis method use is descriptive analysis and statistical analysis through multiple regression test, correlation coefficient, coefficient of determination, t test and f test. The results of this study indicate that compensation and competence partially and simultaneously have a positive and significant effects and employee perfomence at the office of maritime affairs and fisheries of Takalar regency.